MENINGKATKAN PEMAHAMAN SISWA MENGGUNAKAN MEDIA BOX AJAIB UNTUK MENGETAHUI HASIL BELAJAR SIFAT-SIFAT BUNYI - Syahmatul Sucandari; Budiyono; Khoirul Fansuri (STKIP Subang, 2024)
This research aims to increase students' understanding of using the Magic Box to determine the learning outcomes of sound properties in class 5A at SDN Gading VII Surabaya. The method used is Classroom Action Research (PTK) with two cycles, where each cycle consists of planning, action, observation and reflection. The subjects of this research were 27 students, data was collected using observation, interviews, tests and documentation. The results of the research show an increase using the Magic Box media. The results from the pre-cycle were 58%, the first cycle was 79% and the second cycle was 85%. This research states that the use of Magic Box media is very effective in improving learning outcomes regarding sound properties material in Natural and Social Sciences Education (IPAS) subjects by creating a fun, interesting learning atmosphere and more active interaction with the group.